WOMEN WRITERS IN ENGLISH LITERATURE - Gulomjonova Shahzoda; Khamitov Eldorbek Erkin ogʻli (TADQIQOTLAR.UZ, 2024)
The article offers comprehensive explanation of female writers in English literature .Throughout history,literature has always been a powerful tool for people from various backgrounds to share their talent for writing with the world. Among these, women, in particular, have played a big part in shaping the literature that we know today with their unique points of view and storytelling skills. They have used literature, sometimes under a pen name (a fake name used to hide their identity), to create characters and stories that have changed how we see the world. Additionally it discusses investigates the significance of female writers among English writers. The findings of this study will be extremely valuable in developing successful and practical methods for teaching English literature in the future. The analysis of world women writers' literary works would illustrate the developments related to women's right to participate in public affairs